Zeolite as a natural adsorbent for nitrogenous compounds removal from water. Issue 1 (February 2021) - Abdulredha, M; Kadhim, N R; Hussein, Ameer H; Almutairi, Mohammad; Alkhaddar, Rafid; Yeboah, David; Hashim, K; AlKhayyat, Ahmed
Abstract: Water is a vital element to the survival of humans and other life forms. Yet, this source is being contaminated due to pollution leading to significantly limited freshwater, which threatens humans' existence. Nitrates and ammonium are water contaminants and their concentration has vividly increased owing to their applications as farm nourishments. High concentrations of such contaminants in water can lead to health issues. Thus, controlling the concentration levels of these pollutants in water grows into the main task for environmentalist. Thus, a natural zeolite filter was employed in this study to minimize the traces of contaminants from water. Samples of synthetic water have been prepared and used in the laboratory tests that contain 50 mg/l of each contaminant. Using natural zeolite dose ranged from 1-5 g/l at various pH level (between 3-10) showed that the zeolite filter significantly improved the water quality for initial concentrations of each pollutant ranged from 10 to 50 mg/l. The outcomes showed that more than 93 % of both contaminates (nitrate and ammonium) were separated after using 5 g/l dose of zeolite in neutral pH level range for 120 minutes.